2018
DOI: 10.1098/rspa.2017.0900
|View full text |Cite
|
Sign up to set email alerts
|

DC dynamic pull-in instability of a dielectric elastomer balloon: an energy-based approach

Abstract: This paper reports an energy-based method for the dynamic pull-in instability analysis of a spherical dielectric elastomer (DE) balloon subjected to a quasi-statically applied inflation pressure and a Heaviside step voltage across the balloon wall. The proposed technique relies on establishing the energy balance at the point of maximum stretch in an oscillation cycle, followed by the imposition of an instability condition for extracting the threshold parameters. The material models of the Ogden family are empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In the latter, bifurcation is possible for the Ogden model [69], but not for the neo-Hookean, Mooney-Rivlin or Gent models. Sharma et al [70] presented an energy-based method for investigating the dynamic performance of inflated, spherically shaped dielectric balloons. In particular, their analysis found that dynamic pull-in instability occurs at larger values of the circumferential stretch than for its static counterpart, the difference depending on the amount of pre-inflation pressure.…”
Section: (C) the Energy Methodsmentioning
confidence: 99%
“…In the latter, bifurcation is possible for the Ogden model [69], but not for the neo-Hookean, Mooney-Rivlin or Gent models. Sharma et al [70] presented an energy-based method for investigating the dynamic performance of inflated, spherically shaped dielectric balloons. In particular, their analysis found that dynamic pull-in instability occurs at larger values of the circumferential stretch than for its static counterpart, the difference depending on the amount of pre-inflation pressure.…”
Section: (C) the Energy Methodsmentioning
confidence: 99%
“…While increasing the sti↵ness, has allowed for higher operational pressures as demonstrated in a study on the Anaconda WEC [156]. For a DEG membrane, the electrical properties can result in additional electromechanical instabilities [157][158][159][160]. To avoid this, DEGs must operate within a certain range before reaching electromechanical instability and dielectric breakdown field as shown in Figure 3(a).…”
Section: Materials Instabilitiesmentioning
confidence: 99%
“…Moreover, the constitutive relations of DEs are nonlinear, such that their instantaneous moduli vary as functions of the electromechanical loads. These features have led to the design of various applications, such as haptic devices (Kim et al, 2016), soft robots (Gu et al, 2018), actuators (Hajiesmaili & Clarke, 2021;Sharma et al, 2018Sharma et al, , 2019Su et al, 2018Su et al, , 2019Kashyap et al, 2020;Sharma et al, 2017;Khurana et al, 2021) and artificial muscles (Lu et al, 2016), that are based on DEs.…”
Section: Introductionmentioning
confidence: 99%